COVID kit adverse effects and mortality in critically ill patients: cross-sectional study - Avilar, Cristina Tavares de Aguiar; Amaral, Thatiana Lameira Maciel; Nascimento , Cawana da Silva do; Andrade, Ítala Maria Araújo; Souza, Gabriel Bezerra de; Kocaçal, Elem; Maraş, Gül Bülbül; Prado, Patricia Rezende do (Online Brazilian Journal of Nursing, 2025)
Objective: To compare the outcomes of the COVID-19 patients who used the COVID Kit in their treatment with those who did not. Methods: This was a single-center, analytical, cross-sectional, and observational study. Results: The study included 49 COVID-19-positive patients; from those, 65.4% were over 50 years old, 50.0% were male, 36.5% were brown, 44.2% obese, and 73.1% had morbidity. Patients who used the COVID Kit had a higher prevalence of altered platelets, creatine phosphokinase, liver function, and cardiac arrhythmias, with significant changes in intestinal function and potassium level. However, mortality proportions were equal between groups. Conclusion: Patients who used the COVID Kit had a higher prevalence of adverse effects, including changes in clinical and laboratory tests. In addition, the COVID-19 Kit did not decrease mortality in these patients.